Low-Voltage Kᵤ-Range Magnetron With Two Outputs of Energy: Design Features and Main Advantages - Churyumov, Gennadiy I.; Wang, Nan-nan; Gerasimov, Volodymyr P.; Li, Wei (IEEE transactions on electron devices, 2020)
This article presents a design of the low-voltage K_{u} -range magnetron with two outputs of energy: an active with matched load and a passive that is matched with a load having reactive impedance and providing frequency tuning (or its adjustment). Studying the magnetron is carried out in continuous and pulsed modes under the following input operating parameters: an operating anode voltage varied in a range of 450-500 V, a magnetic field of 0.25 T, a pulse length of 5-20 μ s, a pulse repetition rate between 100 and 300 Hz, and the magnetron weight ~0.85 kg subject to air cooling. The results of computer modeling the mode spectrum of a cold resonant anode block of the magnetron show that the separation between the operating N/2-mode and the closest low-voltage (N/2-1)-mode is ~1.6 GHz. Under these conditions, it is shown that the maximum frequency tuning of the cold resonant anode block is ~250 MHz. It is shown that the results of experimental studies of frequency tuning in the magnetron depend on the value of reactive loading in the second (passive) output. The limiting value of the frequency tuning range of the "hot" magnetron is ~110 MHz, providing an output average power of 15 W at ~36% efficiency. The available results of computer modeling are in good agreement with the experiment data. The implementation of the mode of frequency tuning enables to extend the functionality of the magnetron and a range of tasks that can be solved.